The Decisive Factors of Choosing Tutorial Institution (Bimbingan Belajar): The Case Study in Ganesha Operations and Sony Sugema College - Kusuma, Rizky Aditya; Gustomo, Aurik (Journal of Business and Management, 2012)
The purpose of this research was to find the factors that become a parent consideration before choosing a Tutorial Institution (Bimbingan Belajar/bimbel). To answer that, Service Quality and Importance-Performance Analysis tool were used in this research. The Service Quality used were divided into 10 dimensions, the 10 dimensions then derived into 32 attributes. The 32 attributes then will be analyzed using Importance-Performance analysis tools that will represents the factors that parents think determine their decisions in choosing bimbel. The research was conducted in two of most recognizable bimbel in Bandung, West Java-Indonesia, the bimbel were Ganesha Operation and Sony Sugema College. There are 120 questionnaire spread using non probability sampling. The research found several important attributes in parent’s point of view. The research also founds that both of the bimbel weren’t performing well in several dimensions. In Ganesha Operations, the tangible dimension, the reliability dimension, the responsiveness dimension and the communication dimension should be improved. Meanwhile in SSC, the tangible dimension, the reliability dimension, and the credibility dimension are the dimension that they should improve. The results then can be used by any of bimbel to improve their performance as there are attributes that were important by the parent’s point of view. Meanwhile, for the bimbel that involved in this research, recommendations were available in the end of paper.Keyword: Tutorial Institution (bimbel), SERVQUAL, Importance-Performance analysis, customer satisfaction.